Social Capital And Climate Change Analysis Through Circular Economy Strategy On Goroho Banana MSME Resilience - Steefra D. Mangkay; Ingrid N. Sembiring; Merry JJ Langi; Yuliana Mose (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Research aims: This study aims to analyze the influence of Social Capital and Climate Change on Business Resilience with the Circular Economy Strategy as a mediator. Design/Methodology/Approach: This study employs a mixed-methods approach, with a dominant quantitative component and supporting qualitative components, to explore the causal relationships among the variables under investigation. It also seeks to test five research hypotheses that are expected to address the research objectives. The sample in this study consisted of 145 SMEs engaged in the processing of Goroho bananas. The samples were distributed across two regencies: Minahasa and North Minahasa. The sample was determined using a purposive sampling method. The criteria for sample selection were SMEs that have been operational for at least three consecutive years. Research findings: The key findings reveal that the Circular Economy Strategy is not merely an operational response, but rather a transformational mechanism that mediates 41-45% of the total impact of Climate Change and Social Capital on Business Resilience, with a statistically significant result (t > 5.2, p < 0.001) and a medium-to-large effect size (f² > 0.23). More importantly, effect size analysis demonstrates that Climate Change and Social Capital have a very substantial practical impact on the adoption of the Circular Economy Strategy (f² > 1.0), indicating that businesses or enterprises facing high climate pressures or possessing strong social networks will dramatically enhance the implementation of circular practices. Qualitative findings reveal the actual dynamics behind statistical figures, showing that the resilience of banana goroho MSMEs is built through real-world experience and collective adaptation. In-depth analysis of the life experiences of banana goroho processing MSME actors reveals that business resilience is genuinely rooted in the foundation of communal values that are deeply ingrained in the lives of the Minahasan community. Social Capital is concretely manifested in mutual aid practices, belief systems passed down through generations, and kinship networks that form a natural safety net when facing external shocks, such as climate anomalies. Empirical evidence shows that, amid crop failures due to unpredictable weather, resource-sharing and knowledge-transfer mechanisms among community members occur without economic calculation—a practice reflecting the local wisdom of "torang samua basudara" (we are all brothers) as a social glue supporting the sustainability of collective endeavors. Theoretical Contribution/Originality: The theoretical contribution of this study lies in the empirical evidence that business resilience in the era of sustainability is not built through a single pathway, but rather through dual pathways—direct and indirect—which require business actors or organizations to transform external challenges into internal capabilities through innovation in circular business models, particularly in the local culinary SME sector. Practitioners/Policy Implications: Based on the research findings, to support business resilience and the implementation of the circular economy in SMEs, policies should include capacity-building for SMEs through training and improved access to resources, as well as incentives for those adopting environmentally friendly practices, such as using recycled materials and reducing waste. Additionally, it is crucial to foster stronger partnerships between the public and private sectors to support the transition of SMEs to a circular economy, along with establishing clear regulations to encourage the adoption of sustainability principles. These measures will enhance the competitiveness of SMEs, help them survive market challenges, and contribute to more sustainable development goals. Research Limitations/Implications: This study focuses on SMEs involved in the processing of Goroho bananas in Minahasa and North Minahasa districts. The study is limited to data from a specific sector; thus, generalization to other industries or geographic contexts should be done with caution.